Acute Myocardial Infarction Following Intravenous Immunoglobulin Therapy in a Young Patient with Guillain–Barré Syndrome - M. Yashwanth; Samarth V. Shetty; Anagha Rao; H. S. Vijay Mahantesh Aradhya; M. Harsha (APIK Journal of Internal Medicine, 2026)
Abstract Intravenous immunoglobulin (IVIG) is widely used for the treatment of autoimmune disorders such as Guillain–Barré syndrome (GBS) and is generally considered safe. However, rare but severe complications such as thromboembolic events, including myocardial infarction (MI), have been reported secondary to IVIG therapy. We describe a 16-year-old previously healthy female diagnosed with GBS who developed acute chest pain 1 h after initiation of IVIG infusion. The electrocardiogram revealed ST-segment elevation in the anterior leads, and cardiac biomarkers were markedly elevated. Thrombolysis with Tenecteplase was successful. Coronary angiography showed normal coronary arteries. IVIG was discontinued, and plasmapheresis was initiated for the management of GBS. This case highlights the rare but life-threatening complication of IVIG-induced MI, even in young patients without cardiovascular risk factors.